Implementasi Program Lentera Baca Desa sebagai Upaya Optimalisasi Minat Baca Anak di Desa Ketapang, Susukan, Semarang - Ervina Septianingsih; Hida Kartika Ratri; Nafisa Nuril Fitriani; Zhalika Ramadhania; Nida Rizqi Nafiah; Annisa Lyla Syahdani; Annisa Utami Luwih Asih; Meydeu Istiqomah Sandy; Muhaimy Nur Rohmat Irvansyah; Nur Miladan (Lembaga Pengembangan Kinerja Dosen, 2025)
The low reading interest among Indonesian children remains a significant challenge that hinders literacy development and reduces the competitiveness of future generations. Ketapang Village, located in Susukan Sub-district, Semarang Regency, is one of the rural areas struggling with limited access to books and the lack of proper literacy facilities. To address this issue, the Community Service Program (Kuliah Kerja Nyata) initiated by university students developed the Lentera Baca Desa program, aiming to establish a child-friendly literacy park accessible to the entire community. The program was implemented through several stages: collecting and managing books obtained from the National Library, organizing a reading space within the Babussalam Mosque area of Kwangsan Hamlet, and officially inaugurating the literacy park in collaboration with local residents. The outcomes indicate that the literacy park not only provides access to reading materials but also creates a conducive and supportive environment that fosters children’s reading interest and strengthens community involvement in educational development. Furthermore, the program highlights that the sustainability and effectiveness of literacy promotion in rural areas rely more on active community participation, collective responsibility, and continuous management efforts rather than solely on the availability of book collections. This initiative demonstrates that grassroots collaboration can be a practical solution to improve literacy culture in underserved areas.